Implementasi Program Pembangunan Infrastruktur Di Desa Paku Kecamatan Morosi Kabupaten Konawe - Pebrianto, Pebrianto; Darpin, Darpin; Elwan, La Ode Muhammad (Universitas Halu Oleo, 2020)
This study aims to determine the implementation of infrastructure development programs in Paku Village, Morosi District, Konawe Regency. as well as to find out the inhibiting factors for infrastructure development in Paku Village, Morosi District, Konawe Regency. This research design is a qualitative descriptive study. To answer the problems in this research, a qualitative descriptive analysis was used. The results of this study illustrate that; 1) The condition of a number of roads in Paku Village, Morosi District, Konawe Regency, until now, almost the entire road from the border of Paku Village is still untouched by the names of asphalt, vaping and so on, the conditions have not changed, still cobbled roads mixed with clay. This can hamper the process of selling natural products in Paku Village and the bad impact can be felt by the community, especially during the rainy season when the freight car cannot operate and 2) that the health facilities in Paku Village are currently inadequate until now, especially puskesmas facilities. According to the author's observations while at the research location that until now the health facility infrastructure has not changed, it can be seen from the number of people who still have to go to the sub-district with a distance of approximately 5 km to get health services.